PENGARUH PEMBERIAN FEEDBACK TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN DITINJAU DARI SIKAP SISWA - TINTIN SUPRIHATIN (Jurnal Evaluasi Pendidikan, 2013)
This study aimed to determine the effect feedback giving toward citizenship education achievement viewed from students' attitudes. The study was conducted in SMAN 45 and 52 with sample consisted of 80 students were taken by multistage random sampling. Data collection was obtained through a questionnaire and achievement test and analyzed using Analysis of Variance (ANOVA) with a two-way design treatment by level 2 x 2. The results showed that: 1) citizenship education achievement on student peer feedback given higher than students who were given teacher feedback, 2) there is an interaction effect between giving feedback and achievement of student attitudes toward citizenship education achievement, and 3) citizenship education achievement in the group of students who have a positif attitude were given peer feedback were higher than those teacher feedback. Based on the research results are expected citizenship education teachers in the learning process by providing feedback using peer feedback.